First record of Aricoris campestris (Bates, 1868) (Lepidoptera: Riodinidae), and occurrence of harmful insects in dragon fruit (Hylocereus polyrhizus) cultivation in the Sertão Pernambucano, Brazil - Rocha , Igor Tenório Marinho da; Simões, Adriano do Nascimento; Silva, José Raliuson Inácio; Carvalho, Maynar Nogueira Rodrigues de; Silveira, Flávio Pereira da Mota; Souza, Remy Farias de; Oliveira, Pedro Ramon Holanda de; Ferreira, Natanael Lucena (Revista de Ciências Agroveterinárias, 2024)
The pitai tree (Hylocereus polyrhizus) is a cacti with great prominence in the current fruit market. It has high rusticity and tolerance to adverse soil and climate conditions and has potential for cultivation in semi-arid regions. Despite being rarely affected by pests, its commercial exploitation can be harmed if control measures are not carried out. Furthermore, phytosanitary products have not been registered for pest control in this crop. Due to this, knowledge of the insects that affect this crop is of fundamental importance for their correct control and the productive success of the orchard. The objective of this study was to carry out an entomofauna survey aiming to evaluate the occurrence of harmful insects in a dragon fruit orchard located in the Pernambuco hinterland. The evaluation took place through photographic records, collection and identification of insects using data in the literature. Records and collections were carried out only during the day. The insects observed were: caterpillar Aricoris campestris (Bates, 1868) (Lepidoptera: Riodinidae), ant Atta sexdens rubropilosa (Forel, 1908) (Hymenoptera: Formicidae), Stingless bee arapuá Trigona spinipes (Fabricius, 1793) (Hymenoptera: Apidae), aphid Myzus persicae (Sulzer, 1776) (Hemiptera: Aphididae). This work reports the first record of A. campestris, ant, arapuá and aphid caterpillars causing damage to the dragon fruit.